2004
DOI: 10.1038/sj.npp.1300553
|View full text |Cite
|
Sign up to set email alerts
|

Brain Metabolites and Cognitive Function among Older Depressed and Healthy Individuals Using 2D MR Spectroscopy

Abstract: Brain metabolites of choline (Ch) and myo-Inisotol (mI) have been reported as elevated among geriatric depressed patients. Twodimensional (2D) magnetic resonance spectroscopy (MRS) provides estimates of Ch, mI, and creatine (Cr) similar to one-dimensional MRS, and it also estimates the resonances of the Ch-containing compounds of phosphoethanolamine (Pe) and phosphocholine (PCh). In this cross-sectional geriatric study, 14 depressed patients and 14 healthy volunteers who were comparable in age, gender, educati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
3

Year Published

2005
2005
2011
2011

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 43 publications
0
6
0
3
Order By: Relevance
“…While arguments may exist on why such approaches would offer better sensitivity than the n-quantum filters in NMR experiments (28), practical aspects of implementing such approaches in clinical scanners (such as relatively large minimum echo times, and a low resolution in the second dimension, to keep acquisition time manageable) have rendered the use of these techniques questionable for routine MRS acquisitions. The reduced repeatability of such measurements reported in vitro (mI CV's of ∼20% reported in Table 2 of (29)) and in vivo (30,31) (mI CV's in excess of 10% reported from data acquired with an SNR level of at least 4 times higher than the highest SNR considered in this report) have led the author to exclude such approaches from the current report. It is also questionable how efficient of a separation between Gly and mI is achievable with these acquisitions, while keeping the acquisition time manageable; overestimation of Gly by 160% and underestimation of mI by ∼20% have been reported in a brain phantom (29), indicating improper separation of the two metabolites.…”
Section: Discussionmentioning
confidence: 93%
“…While arguments may exist on why such approaches would offer better sensitivity than the n-quantum filters in NMR experiments (28), practical aspects of implementing such approaches in clinical scanners (such as relatively large minimum echo times, and a low resolution in the second dimension, to keep acquisition time manageable) have rendered the use of these techniques questionable for routine MRS acquisitions. The reduced repeatability of such measurements reported in vitro (mI CV's of ∼20% reported in Table 2 of (29)) and in vivo (30,31) (mI CV's in excess of 10% reported from data acquired with an SNR level of at least 4 times higher than the highest SNR considered in this report) have led the author to exclude such approaches from the current report. It is also questionable how efficient of a separation between Gly and mI is achievable with these acquisitions, while keeping the acquisition time manageable; overestimation of Gly by 160% and underestimation of mI by ∼20% have been reported in a brain phantom (29), indicating improper separation of the two metabolites.…”
Section: Discussionmentioning
confidence: 93%
“…Wyckoff and colleagues (2003) also reported increased myo-inositol concentrations in the left dorsolateral white matter of unmedicated late-life MDD patients. Moreover, a recent study correlated the increase in left dorsolateral prefrontal cortex myoinositol with increased cognitive function in healthy volunteers by not in late-life MDD patients (Elderkin- Thompson et al, 2004). In contrast, in a similar studies, no differences in frontal lobe myo-inositol concentrations were found between unmedicated MDD patients and healthy controls (Gruber et al, 2003a;Binesh et al, 2004).…”
Section: Major Depressive Disordermentioning
confidence: 90%
“…Among nondepressed subjects, cognition positively correlated with Cho/Cr and mI/Cr and negatively correlated with phosphocholine/Cr in four domains of verbal learning, recognition, recall, and hypothesis generation, whereas, depressed patients did not have consistent relationships between the metabolites. (89) Thus imaging studies have revealed both neuroanatomic as well as biochemical changes in the frontostriatal circuitry that may be associated with cognitive changes in depression.…”
Section: White Matter Pathologymentioning
confidence: 99%